GKB - Geographic Knowledge Base - Chaves, Marcirio Silveira (2009)
This paper introduces GKB, a repository based on a domain-independent meta-model for integrating geographic knowledge collected from multiple sources. We present the architecture, the repository design and the data cleaning and knowledge integration processes. We also describe the rules developed to add new knowledge to the repository. GKB includes tools for generating ontologies, which are being used by multiple Semantic Web applications. In addition GKB supports multiple languages. To illustrate how it is being used, we describe some applications that interact with the repository or load the generated ontologies